Adaptive Quality Management in Modern Islamic Boarding Schools: Evidence from Muslim-Minority Communities in Southern Thailand - Anas Laerosa; Mustaqim Mustaqim; Fakhrurrozi Fakhrurrozi (Journal of Counseling, Education and Society, 2025)
This study aims to analyze adaptive quality management in modern Islamic boarding schools in the context of minority Muslim communities in Southern Thailand, focusing on how Islamic educational institutions negotiate the demands of external change with the preservation of institutional identity. The research uses a qualitative approach with a case study design on Ma'had Mesbah El-Ulum and Muassasah Asshakafah Al-Islamiah in Southern Thailand. Data were obtained through in-depth interviews, participatory observations, and documentation of actors who have direct experience in education quality management practices. Data were analyzed iteratively through open coding, thematic categorization, abstraction, and interpretive synthesis to identify patterns of adaptation as well as emerging institutional mechanisms. The findings show that adaptive quality management does not operate solely as a technical response to education policy, but as a negotiation process between external institutional demands and the reproduction of internal identities. Curriculum flexibility, strengthening Arabic and English, digital literacy, and adjustments to national education standards allow pesantren to accumulate cultural capital that is relevant to the educational arena and the job market, while maintaining Islamic values as a source of symbolic legitimacy. These findings indicate the emergence of a hybrid educational identity, in which modernization does not replace religious identity, but is negotiated through the integration of various forms of capital. The contribution of the research lies in the conceptual development of adaptive quality management as a negotiation mechanism between identity preservation, institutional adaptation, and capital conversion, thereby expanding the understanding of how Islamic educational institutions in minority contexts can maintain social legitimacy while increasing the academic relevance and employability of students